Self-regulating platforms? The Analysis of the Enforcement of End-user Rights in the Light of the Transposition of Article 17 of the CDSM Directive - Mezei, Péter; Harkai, István (Public Governance, Administration and Finances Law Review, 2022)
The deadline for the transposition of Directive (EU) 2019/790 (the CDSM Directive) into national law expired on 7 June 2021. Some EU Member States have failed to perform the transposition, and so they also failed to introduce the new obligations under Article 17 prescribing brand new requirements that online content-sharing service providers (OCSSPs) shall comply with. As a part of these rules, OCSSPs shall amend their end-user licence agreements (EULAs) to include terms on the enforcement of the mandatory limitations and exceptions (quotation, criticism, review, as well as use for the purpose of caricature, parody and pastiche) under Article 17(7) and the establishment of an effective complaints and redress mechanism regarding the removal of the user-generated content in line with Article 17(9). In the second phase of our ongoing EU-funded research project, we examined the extent to which specific OCSSPs have amended their EULAs to meet these EU obligations. Our empirical data show that, besides only little progress, new sources of conflict have emerged.